Anigosomphus yanagisawai sp. nov., a new gomphid dragonfly from northern Thailand (Odonata: Anisoptera: Gomphidae) - Sasamoto, Akihiko (Zootaxa, 2015)
A new species of Anisogomphus Selys, A. yanagisawai sp. nov. (holotype male and paratype specimens) from N. Thailand (Doi Inthanon, ca. 1,400 m a.s.l., Ban Luang, Chiang Mai Prov.), is described and illustrated. This species can apparently be distinguished from the other species of this genus by the morphology of the anal appendages, especially the straight cerci closely disposed to each other and bearing a very strong outer branch.